Invalidation of Microsomal Prostaglandin E Synthase-1 (mPGES-1) Reduces Diet-Induced Low-Grade Inflammation and Adiposity - Pierre, Clément; Guillebaud, Florent; Airault, Coraline; Baril, Nathalie; Barbouche, Rym; Save, Etienne; Gaigé, Stéphanie; Bariohay, Bruno; Dallaporta, Michel; Troadec, Jean-Denis (Frontiers in Physiology, 2018)
Chronic low-grade inflammation is known to be linked to obesity, and to occur in the early stages of the disease. This mechanism is complex and involves numerous organs, cells, and cytokines. In this context, inflammation of white adipose tissue seems to play a key role in the development of obesity. Because of its properties, prostaglandin E2 (PGE2), an emblematic inflammatory mediator, has been proposed as an actor linking inflammation and obesity. Indeed, PGE2 is involved in mechanisms that are dysregulated in obesity such as lipolysis and adipogenesis. Microsomal prostaglandin E synthase-1 (mPGES-1) is an enzyme which specifically catalyzes the final step of PGE2 biosynthesis. Interestingly, mPGES-1 invalidation dramatically alters the production of PGE2 during inflammation. In the present work, we sought to determine whether mPGES-1 could contribute to inflammation associated with obesity. To this end, we analyzed the energy metabolism of mPGES-1 deficient mice (mPGES-1-/-) and littermate controls, fed with a high-fat diet. Our data showed that mPGES-1 -/- mice exhibited resistance to diet-induced obesity when compared to wild-type littermates. mPGES-1-/- mice fed with a high-fat diet, showed a lower body weight gain and a reduced adiposity, which were accompanied by a decrease in adipose tissues inflammation. We also observed an increase in energy expenditures in mPGES-1-/- mice fed with a high-fat diet without any changes in activity and browning process. Altogether, these data suggest that mPGES-1 inhibition may prevent diet-induced obesity.